Answer:
147
Step-by-step explanation:
if you multiply by .40 then subtract that from 245 you get 147
Let x be the 1st odd number, and x+2 the second odd consecutive number:
(x)(x + 2) = 6[((x) + (x+2)] -1
x² + 2x = 6(2x + 2) - 1
x² + 2x = 12x +12 - 1
And x² - 10x - 11=0
Solve this quadratic expression:
x' = [+10 +√(10²- 4.(1)(-11)]/2 and x" = [+10 -√(10²- 4.(1)(-11)]/2
x' = [10 + √144]/2 and x" = [10 - √64]/2
x' = (10+12)/2 and x" = (10-12)/2
x = 11 and x = -1
We have 2 solutions that satisfy the problem:
1st for x = 11, the numbers at 11 and 13
2nd for x = - 1 , the numbers are -1 and +1
If you plug each one in the original equation :(x)(x + 2) = 6[((x) + (x+2)] -1
you will find that both generates an equlity
Answer:
The car dealer must sell 105 cars in May to reach his goal.
Step-by-step explanation:
Given that the car dealer sold 84 cars in April, and wants to increase his May sales by 25%, to determine the number of cars he must sell to reach his goal it is necessary to perform the following calculation:
84 + (84 x 0.25) = X
84 + 21 = X
105 = X
Therefore, the car dealer must sell 105 cars in May to reach his goal.
Answer:
Step 2
Step-by-step explanation:
Step 2 is not correct. It should be abs(25 - - 26) = abs(25 + 26) = 51
Given that Step 2 is accepted (as - 1) then three is OK and and so is 4. But technically they are incorrect as well. I think you are likely to say that step 2 is the problem.
Answer:
The correct answer is D. (-1,3)